ANALYSIS OF COMPLICATIONS AFTER AUTOGRAFT TRANSPLANTATION IN SEVERE UPPER LIMB INJURY - G.D. KARIM-ZADE (Avicenna Tajik State Medical University, 2023)
Objective: To analyze the complications after transplantation of vascularized autografts in upper limb injuries and develop a set of measures to eliminate them. Methods: Surgical treatment outcomes of 159 patients with severe upper limb injury sequelae were analyzed. The study population comprised 102 (64.1%) males, 57 (35.8%) females, and 49.6% of the patients were under 18. In forearm and hand injuries sequelae, 159 vascularized skin fascia and skin-bone composite autograft flaps were used. Of the 159 grafts, free flaps grafting and pedicled flaps grafting were performed in 30 (18.8%) and 129 (81.2%), respectively. Results: Of 30 free flaps, circulatory compromise was observed in 4 (13.3%) cases in the early postoperative period. Out of the total 159 grafts used, the percentage was 2.5%. In evaluating complications, it was revealed that the flap circulatory compromise of 4 patients was noted in the following grafting types: radial osseocutaneous (1), radial fasciocutaneous (1), fibula transplant (1), and inguinal fasciocutaneous (1). Of the 129 reverse and transposition flaps, a circulatory compromise was noted in 10 (7.7%) cases. Out of the total 159 flaps, the percentage of circulatory compromise was 6.3%. Of the total 159 free and pedicled flaps, necrosis with flap loss was observed in 6.9%. Conclusion: Timely diagnosis of complications based on clinical and axillary investigations data facilitated conducting appropriate conservative measures or surgical revision, which helped to achieve engraftment of transplanted autografts in 93.1% of cases.